PENGARUH LINGKUNGAN KERJA DAN PELATIHAN TERHADAP KINERJA KARYAWAN PTPN VI UNIT OPHIR SARIAK - Hendri Rosa (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2015)
The production of oil palm plantations , CPO (Curt Palm Oil), has been a mainstay of the economy of Indonesian commodities. In order to continue to rise the CPO production, the oil palm plantation company, must be able to increase production. So that the company is able to produce at an optimum level, necessary to support high-performing employees. This study to analyzed the effect of environment and training on employee performance on PTPN VI Ophir unit. The study population overall employee of PT. PTPN VI Ophir Unit as 625 people. The number of samples is set as 87 people based on Slovin formula. Measurement of variables with quantitative instruments with Likert scale. Hypothesis testing with multiple linear regression find the results that the environment has a positive and significant impact on employee performance with a coefficient of 0.384 and a significance value of 0.003 (